Suppressive effect of rutin on methotrexate- induced salivary gland injury in rats - Attarbashee, Rana Khairi; Al-Athari, Ali Jihad Hemid; Shihab, Elaf Mahmood; Ridha-Salman, Hayder; Zigam, Qassim A.; Abbas, Weaam J.; Abbas, Alaa Hamza; Raheem, Abdulla K.; AbdulAemah, Maytham Ahmed; Hassan, Zaid M.; Abbas, Saba Naseer; Shareef, Saja Majeed (Pharmakeftiki, 2025)
Methotrexate is an antimetabolite used in the treatment of various cancers and autoinflammatory disorders. However, it can adversely affect oral tissues, particularly impairing salivary gland function. The antioxidant and anti-inflammatory effects of rutin may counteract these toxic effects. This study aimed at examining whether rutin confers protective effects on the salivary glands of rats exposed to methotrexate. Twenty-four male rats were randomly assigned to three groups. The control group received normal saline intraperitoneally for 10 days. On day six of the experiment, the methotrexate group was administered methotrexate intraperitoneally at a dose of 20 mg/kg. The methotrexate + rutin group also received rutin intraperitoneally at 50 mg/kg once daily for 10 days. On day 11, the animals were euthanized, and their salivary gland tissues were harvested for histological and biochemical analyses. Rutin markedly ameliorated the methotrexate-induced histopathological changes and biochemical alterations, as indicated by reduced levels of the tumour necrosis factor-α and malondialdehyde, alongside elevated levels of interleukin-10 and superoxide dismutase. These findings suggest that the antioxidant and anti-inflammatory properties of rutin may offer a promising strategy for mitigating the methotrexate-associated toxicity in submandibular gland tissues.